Treatment efficacy with electrochemotherapy: A multi-institutional prospective observational study on 376 patients with superficial tumors. Issue 12 (December 2016) - Campana, L.G.; Testori, A.; Curatolo, P.; Quaglino, P.; Mocellin, S.; Framarini, M.; Borgognoni, L.; Ascierto, P.A.; Mozzillo, N.; Guida, M.; Bucher, S.; Rotunno, R.; et al.
Abstract: Background: Cutaneous metastases represent a therapeutic challenge. An increasing body of experience suggests that electrochemotherapy (ECT) provides effective tumor control, although its evidence basis should be strengthened. Methods: This prospective, multicenter, observational study enrolled patients with superficial metastases, who underwent ECT at 10 centers between 2008 and 2013. Outcomes included adherence to European Standard Operating Procedures of ECT (ESOPE), tumor response, local progression-free survival (LPFS), toxicity and patient-reported outcomes (PROs, EORTC QLQ-C30 plus an 8-item questionnaire). Results: We enrolled 376 eligible patients. Tumor histotype distribution was as follows: melanoma, 56%; squamous cell carcinoma, 11%; Kaposi sarcoma, 11%; breast carcinoma, 8%; basal cell carcinoma, 6%; soft tissue sarcomas, 3%; others, 5%. We registered 1304 target tumors (median size 1 cm). Treatment adhered to ESOPE in 88% of patients as to the route of drug administration, and in 70% as to electrode application. The procedure was mainly performed under sedation (64.6%) and by using intravenous chemotherapy (93.4%). Tumor response rate at 60 days was 88% (complete, 50%). Small tumor size predicted complete response achievement (OR 2.24, p = 0.003), higher LPFS (HR 0.68, p = 0.004) and improved PROs (Global Health Status, p < 0.001; wound bleeding, p < 0.001; healing, p = 0.002; and aesthetics, p < 0.001). Skin toxicity (grade ≥3, 7.8%) was lower in patients with tumors <2 cm ( p ≤ 0.001 ). One-year LPFS was 73.7% (95%CI 68.4–78.3). Conclusions: ECT represents a valuable skin-directed therapy across a range of malignancies. The most frequently applied treatment modality is intravenous chemotherapy under sedation. Small tumor size predicts durable tumor control, fewer side-effects and better PROs.